Leituras sobre o problema da morte nos Ensaios de Michel de Montaigne - Tiago Barros Duarte (2012)
The analysis of the most important texts that deal with the issue of death in the Essays of Michel de Montaigne is the aim goal of this work. Starting from this analysis, we investigate what are the ways of dealing with death that the French thinker recommends to his lector. We also search, dialoging with some of his main interpreters, to identify the causes for the changes in those recommendations along his book, as well as the reason of the lack of considerations about the thesis of the immortality of the soul in these texts. Finally, we argue about the comprehension of Montaignes philosophy of death as an essentially moral reflection, directed above all to the wellbeing of men.